The Effect of Information and Subsidy Measures on Adoption of Solar Lanterns : An Application of the BDM Bidding Mechanism in Rural Ethiopia - Mekonnen, Alemu; Hassen, Sied; Jaime, Marcela; Toman, Michael A.; Zhang, Xiao-Bing (World Bank, Washington, DC, 2021)
Solar lanterns are a relatively inexpensive renewable-energy option for household lighting in developing countries. However, the transition to these lighting sources is slow. To understand why, this study uses the Becker-Degroot-Marschak bidding mechanism in a randomized field experiment to investigate the effect of information provision and subsidy policy instruments on the uptake of solar lanterns. Subjects’ willingness to pay tends to be low enough that most of them would purchase the solar lantern only if it is subsidized. Households with access to grid electricity have a lower willingness to pay and are less likely to adopt, while those using kerosene as a source of lighting are more likely to adopt. Access to credit also increases willingness to pay. Information treatments have limited impact: provision of different types of information about the private and public benefits of solar lantern use increases adoption only when it is combined with a high level of subsidies. Given the relatively low cost of solar lanterns, the results suggest that achieving universal electricity access under the United Nations’ Sustainable Development Goals by any means will require subsidizing access.